Psycho-environmental analysis of public urban spaces: squares and parks - Velásquez Marea, Carmen V. (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2008)
This article presents a psycho-environmental analysis of public spaces - squares and parks, located inside the urban perimeter of the city of Maracaibo, Venezuela. The analysis considers aspects related to the urban climate of the city (warm and humid), the physical characteristics and micro-climatic of the spaces, the thermal and social comfort of the users, and the determination of the urban image of the spaces starting from the identity, structure and ideal image. It was based on the meteorological data coming from a local urban station, as well as on some climatic variables and qualitative data related to the spaces. The results show a clear relationship between the use of the spaces and the local climatic conditions and the necessity of generating shady spaces to provide better comfort conditions. Moreover, the study indicated that the urban image of those spaces is associated to the presence of atypical activities and elements, the equipment, the benefit of services, and the vegetation presence.